2019
DOI: 10.1016/j.jcol.2018.10.003
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy of low residue enteral formula versus clear liquid diet during bowel preparation for colonoscopy: a randomised controlled pilot trial

Abstract: Objectives  Conventional bowel preparation for colonoscopy confines patient to clear liquid diet the day before and such non-nutritive dietary regimen often caused discomfort and hunger. The purpose of this study is to determine the feasibility of feeding patient with low-residue, lactose-free semi-elemental enteral formula (PEPTAMEN®) compare to conventional clear liquid diet during bowel preparation before colonoscopy. Methods  This was a randomised, endoscopist-blinded study. P… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 17 publications
0
5
0
Order By: Relevance
“…The analysis showed that a total of 5 studies (N = 933) involved the indicator of hunger. [ 13 , 15 , 19 , 21 , 26 ] In the pooled analysis, the hunger sensation in the CLD group (52.5%, 244/465) was significantly more severe than that in the LRD group (36.8%, 172/468). (RR, 1.64, 95% CI, 1.12–2.39; P < .05; I 2 = 81.4%, P < .01) (Fig.…”
Section: Resultsmentioning
confidence: 96%
“…The analysis showed that a total of 5 studies (N = 933) involved the indicator of hunger. [ 13 , 15 , 19 , 21 , 26 ] In the pooled analysis, the hunger sensation in the CLD group (52.5%, 244/465) was significantly more severe than that in the LRD group (36.8%, 172/468). (RR, 1.64, 95% CI, 1.12–2.39; P < .05; I 2 = 81.4%, P < .01) (Fig.…”
Section: Resultsmentioning
confidence: 96%
“…Of the eligible articles, 12 ( n = 2205) ( Alvarez-Gonzalez et al, 2019 ; Butt, Bunn, Paul, Gibson, & Brown, 2016 ; Flemming, Green, Melicharkova, Vanner, & Hookey, 2015 ; Gee et al, 2019 ; Melicharkova, Flemming, Vanner, & Hookey, 2013 ; Mytyk et al, 2018 ; Rapier & Houston, 2006 ; Scott et al, 2005 ; Soweid et al, 2010 ; Stolpman et al, 2014 ; Thukral et al, 2019 ; Walter et al, 2017 ) evaluated the number of participants who achieved excellent or good bowel preparation. These studies used the BBPS, Aronchick Scale, or HCS to determine the eligibility criteria.…”
Section: Resultsmentioning
confidence: 99%
“…As shown in Figure 4 , six studies ( Alvarez-Gonzalez et al, 2019 ; Flemming et al, 2015 ; Gee et al, 2019 ; Gomez-Reyes et al, 2019 ; Stolpman et al, 2014 ; Walter et al, 2017 ) examined the polyp detection rates (PDRs), which were similar between the LRD and CLD groups (50.8% vs. 49.1%; OR [95% CI] = 1.07 [0.83, 1.38]; p = .60). Heterogeneity among the groups was not significant ( I 2 = 36%; p = .16).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The bowel preparation quality was assessed by the examiner based on modified Aronchick scale (Table 2 ). [ 8 , 9 ] We defined bowel preparation quality as “good preparation” if it corresponded to modified Aronchick scale “Excellent” or “Good”. We also defined the quality as “adequate preparation” if it corresponded to “Excellent”, “Good”, or “Fair”.…”
Section: Methodsmentioning
confidence: 99%